Análise dialélica para dry down e qualidade industrial em grãos de milho na segunda safra - Friske, Élcio (2021)
In the last 10 years, there was a significant increase in corn production costs and a lower profitability for the grain producer due to discounts in the corn price caused by kernel moisture and damage. In this sense, minimizing these losses though the search for new dry down cultivars and that present low damage rates can improve the profitability for the grain producer, as well as increase the feed quality in the milling industry. This study was to identify maize parents and hybrids with rapid dry down and better industrial quality of maize grain for the feed industry for the development of new cultivars. In this respect, a partial diallel cross with 16 lines was conducted in the second crop season of 2019 in two environments (Londrina, PR and Santa Tereza do Oeste, PR) in experimental areas of the IDR-Paraná to evaluate the performance of the hybrids and obtain estimates of combining ability for dry down (DD), grain yield (GY), total damage (TD), cracking rate (CR), indentation (INDEN), fine fractions according to particle size (FF) and protein content (PROT) evaluated by NIRS (Near Infrared Spectroscopy) at Embrapa Milho e Sorgo in a randomized block design with two replications. Data analysis was performed via the mixed model approach, REML/BLUP, and t-BLUP’s were calculated to verify the significance of the BLUP’s of the parents and hybrid combinations. Graph representations were formed for better visualization of the genetic values and general combining ability (GCA) of the maize hybrids in combined by environments for all the traits. The combined diallel analysis showed that the additive effects were more important for six of the traits, though not for CR, which highlight the importance of selecting superior lines for this trait. Two parents stood out in both locations: the parent L3 was most promising for yield, and the parent L5 was superior for protein. The specific combining ability (SCA) of hybrids among dent type texture and flint type texture showed relevant information regarding IDEN, which can help the conduction of new breeding populations that aim at a better quality of swine and poultry feed, respectively, directed to use of hybrids with better quality and yield for the grinding industry.